2013
DOI: 10.1111/adj.12099
|View full text |Cite
|
Sign up to set email alerts
|

A laboratory investigation of colour changes in two contemporary resin composites on exposure to spices

Abstract: Background: The aim of this study was to evaluate colour stability upon exposure to spices of a nano-filled and a microhybrid resin composite finished either with Sof-Lex TM discs (SLD) or against plastic strips (PS). Methods: Forty cylindrical specimens of 3 mm thickness were fabricated from Filtek Supreme XT TM (FS) and Gradia Direct X TM (GD). The top surface of each specimen was polished with SLD while the bottom surface was finished against PS. All samples were immersed in staining solutions (0.1% weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 30 publications
1
18
0
1
Order By: Relevance
“…There has been no article that evaluated the staining potential of these beverages on dental resin composites. Only in a few studies, some spices' staining potential on dental resins was evaluated, but, in these studies, only 1% solutions 14 or extracts were used, 21 and no beverages were evaluated. Yew et al 14 evaluated the discoloration of two contemporary composites on exposure to spices of 0.1% weight, i.e., turmeric, paprika, and tamarind, and they reported that turmeric significantly stained the resin composites, but tamarind slightly and only after 168 hours affected the color of the resin composites.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There has been no article that evaluated the staining potential of these beverages on dental resin composites. Only in a few studies, some spices' staining potential on dental resins was evaluated, but, in these studies, only 1% solutions 14 or extracts were used, 21 and no beverages were evaluated. Yew et al 14 evaluated the discoloration of two contemporary composites on exposure to spices of 0.1% weight, i.e., turmeric, paprika, and tamarind, and they reported that turmeric significantly stained the resin composites, but tamarind slightly and only after 168 hours affected the color of the resin composites.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] However, there are some different kinds of beverages, such as traditional ones, which may have probable staining potential. Tamarind syrup, ottoman syrup, and turnip juice are some traditional Turkish beverages.…”
Section: -15mentioning
confidence: 99%
See 2 more Smart Citations
“…Paprika and tamarind that are widely used in other Asian foods have also been evaluated recently. 9 Saffron is one of the most expensive spices but a widely used one in Indian foods for flavor and color. 10 Thus, the current study was done to assess the color stability of nanohybrid resin-based direct composites and indirect resin composites to Indian spices such as turmeric, tamarind, paprika, and saffron.…”
Section: Introductionmentioning
confidence: 99%